Investigation of the incidence and causes elite tennis players` injuries in Turkey - Sener, O. A.; Cinar, S.; Ziylan, T. (Turkish Journal of Sport and Exercise, 2016)
Is a sport branch forcing technical, tactical, physiological and psychological capabilities of human is one of the best sports branches. "Sports Injuries" is referred to every kind of damage occurring during sportive activities. Several factors are involved in sports injuries including age, quality of the material used, weather, lighting, court, hall, component, physical condition of the athlete etc. In addition, psychological factor have also been stated to play a role in sports injuries. The study was performed with a questionnaire conducted on 86 elite male tennis players who were playing in Ankara, Konya and Istanbul regions at 1990-1991 season of Turkey Tennis Classification League. In study, 47 players have exposed to injury, while 39 have not. Rates of injuries were found to be higher in the shoulder, elbow, knee and ankle regions compared to the other parts of the body. In conclusion, in this study we found that the incidence of injury was 54.65% among male tennis player. In addition, our findings indicated that stressful events experienced by the tennis players were also effective on injuries.